2011
DOI: 10.1152/physiol.00043.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Athlete's Heart vs. the Failing Heart: Can Signaling Explain the Two Distinct Outcomes?

Abstract: Cardiac remodeling is typically associated with disease and can lead to heart failure. In contrast, remodeling that occurs in the athlete's heart is considered an adaptive physiological response. This review provides an overview of signaling mechanisms responsible for inducing left ventricular hypertrophy in the athlete's heart and in settings of pathological hypertrophy and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 111 publications
6
114
0
7
Order By: Relevance
“…Akt1 is phosphorylated in physiological cardiac hypertrophy and exerts diverse beneficial functions such as inhibition of cardiomyocyte apoptosis, improvement in calcium transients, and cardiac hypertrophy (46,62). A series of studies led by the McMullen's group (63,64,98) has shown the role of insulin-like growth factor 1 (IGF-1)/IGF-1 receptor (IGF-1R)/PI3K (110␣) in the development of physiological cardiac hypertrophy. *Predicted target gene.…”
Section: Mirnas Cardiac Hypertrophy and Exercise Trainingmentioning
confidence: 99%
“…Akt1 is phosphorylated in physiological cardiac hypertrophy and exerts diverse beneficial functions such as inhibition of cardiomyocyte apoptosis, improvement in calcium transients, and cardiac hypertrophy (46,62). A series of studies led by the McMullen's group (63,64,98) has shown the role of insulin-like growth factor 1 (IGF-1)/IGF-1 receptor (IGF-1R)/PI3K (110␣) in the development of physiological cardiac hypertrophy. *Predicted target gene.…”
Section: Mirnas Cardiac Hypertrophy and Exercise Trainingmentioning
confidence: 99%
“…The adult heart can adapt to stress by hypertrophy and vascular growth/remodeling (Bernardo et al, 2010;Weeks KL and McMullen JR, 2011). Physiological or adaptive responses, as in the case of the exercised trained athelete's heart, are characterized by balanced changes in both the cardiomyocytes and the vasculature.…”
Section: Regulating the Coronary Vessels Within The Adult Heart For Cmentioning
confidence: 99%
“…The physiological and pathological responses overlap in some respects, especially in the early stages of adaptation. However, there are distinct characteristics to the physiological and pathological responses that have been revealed by studies in humans and rodent models (Boström P et al, 2010;Pavlik G et al, 2010;Weeks KL and McMullen JR, 2011). These differences include the degree of vascularization of the myocardium with the physiological response leading to increased vascularization.…”
Section: Regulating the Coronary Vessels Within The Adult Heart For Cmentioning
confidence: 99%
“…Increased workload, such as during exercise or chronic disease stresses causing pressure overload, induces cardiomyocyte hypertrophy, while hemodynamic unloading leads to heart atrophy (1)(2)(3). Such changes in cell size depend on the equilibrium between the rates of protein synthesis and degradation, both of which are finely regulated by a number of signaling pathways and require a tight control over protein turnover and protein quality control to avoid accumulation of unfolded/ misfolded proteins and subsequent ER stress (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%